PEDAGOGICAL VALUES IN PENCAK SILAT EXTRACURRICULAR ACTIVITIES FOR DEVELOPING ELEMENTARY SCHOOL STUDENTS' CHARACTERS AT SDN 2 PANGEUREUNAN - Mohamad Faisyal; Juntika Nurihsan; Babang Robandi (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Pencak Silat is an educational material aimed at shaping individuals who are capable of performing beneficial actions and behaviors to establish mutual security and welfare. The purpose of this research is to analyze the influence of pedagogical values on extracurricular Pencak Silat activities in developing the character of elementary school students at SDN 2 Pangeureunan. The method used in this research is descriptive qualitative. A qualitative approach was chosen because it was deemed suitable for the problem focused on in this research. The results of this research show that the planning of character development programs for students at SDN 2 Pangeureunan through extracurricular Pencak Silat activities is developed by the curriculum development team formed by the school principal as the program's responsible party. Other character values that emerged in addition to the five main characters set at SDN 2 Pangeureunan are the values of hard work, curiosity, social care, friendliness, communicativeness, responsibility, respect, love of the homeland, appreciation of achievements, love of peace, and democracy. Therefore, character value development through extracurricular Pencak Silat activities not only develops the five main character values but also other excellent character values in shaping students to have good and superior personalities